2008
DOI: 10.1007/978-3-540-85990-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Acquisition Schemes in High Angular Resolution Diffusion Weighted Imaging

Abstract: Abstract. The recent challenge in diffusion imaging is to find acquisition schemes and analysis approaches that can represent non-gaussian diffusion profiles in a clinically feasible measurement time. In this work we investigate the effect of b-value and the number of gradient vector directions on Q-ball imaging and the Diffusion Orientation Transform (DOT) in a structured way using computational simulations, hardware crossing-fiber diffusion phantoms, and in-vivo brain scans. We observe that DOT is more robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…For the DOT, we use R 0 = 12 μm . Although higher values can yield a better resolution accuracy, they result in a little robustness to noise, as it has been pointed out by Prčkovska et al (2008). Hence, R 0 = 12 μm is preferable in real-world scenarios (Özarslan et al, 2006), and it is the trade-off used in all our experiments.…”
Section: Methodsmentioning
confidence: 88%
“…For the DOT, we use R 0 = 12 μm . Although higher values can yield a better resolution accuracy, they result in a little robustness to noise, as it has been pointed out by Prčkovska et al (2008). Hence, R 0 = 12 μm is preferable in real-world scenarios (Özarslan et al, 2006), and it is the trade-off used in all our experiments.…”
Section: Methodsmentioning
confidence: 88%
“…Noise as measured by SNR had more of an effect on smaller direction sets (ie, 12, 16) sets than larger (ie, 32, 64) sets. The AC represents a relatively new metric in the domain of QBI reconstructions, which has been demonstrated as a necessary metric for QBI-based probabilistic tractography (31,32). AC values showed that the diffusion tensor PEV and the ODF PDV may be subject to an error that biased their orientations by as much as 60 for highly corrupt 32-and 64-direction data cases.…”
Section: Discussionmentioning
confidence: 99%
“…For larger direction sets, as well as for Err-gFA in the case of QBI, the impact of noise on metrics was less apparent. Impacts of noise on DWI measurements have previously been investigated by several authors (23,31).…”
Section: Impact Of Snr Variation: Dti/qbimentioning
confidence: 99%
“…A different approach studies DTI (and HARDI) data sets, where several measurements in multiple imaging directions are available. These multiple readings allow one to construct a distribution of possible values, and an estimation of noise related to the choice of b value [13, 46, 12, 17, 38], the registration [41, 23], the model fitting [1, 39, 30, 51, 24], the maximum finding, decomposition, or enhancement [25, 43, 22, 38, 42], or the fiber tracking algorithms [18, 10, 14, 36, 54, 26, 12]. …”
Section: Related Workmentioning
confidence: 99%